Diagnoza ekonomiczno-finansowa sektora przedsiębiorstw w Polsce - Famielec, Józefa (The Diagnosis of Financial and Economic Condition of the Corporations Sector in Poland, 2005)
In this report is discussed the range of the corporations sector in Poland and its financial result for years 1995-2002, including the major branches of national economy and also the structure of property. It is stated that the corporations sector require restructuring, particularly in the aspect of finances. This report indicates the major procedures of conducting alterations to the structure of corporations finances. They apply in particular to the mining and metallurgical industry and also to major enterprises, which play the important role on the labour market. At present of significance for restructuring enterprises is the new law of bankruptcy, which will be valid from 1.10.2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 76-88